Workshop on Implementing the Problem Based Learning With Communicative Games (Pbl-Cg) Model for English Teachers in Elementary Schools - Kurniati, Erisa; Fitri, Nurul; Kumalasari, Ade (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2024)
This workshop aims to provide training to English Language Education Study Program students and teachers at SD 205/IV Jambi City. The author presents the PBL-CG (Problem-Based Learning with Communicative Games) model for workshop activities. This model is an improved version of the previous PBL model for teaching English at elementary schools. The workshop method includes three steps: identifying partner priority problems, justifying the priority problems, and defining work procedures. The work procedure involves preparation, implementation, and reporting stages. The two-day workshop was held at SD N 205/IV Jambi City, and the English teachers were enthusiastic and participated actively. The participants well-absorbed the training material, as evidenced by the higher average score in the posttest evaluation. The workshop successfully equipped participants to prepare lesson plans based on the 2013 curriculum using the PBL-CG model in the English language learning process at school, along with the assessment rubric.